Application of differential games in mechatronic control system - Hendzel, Zenon; Penar, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Differential games are a combination of game theory and optimum control methods. Their solutions are based on Bellman's principle of optimality. In this paper, the zero-sum differential game theory has been used for the purposes of controlling a mechatronic object: a single-link manipulator. In this case, analytical solutions are unavailable, thus approximate solutions were used. Two approximation methods were compared with the use of numerical simulations and selected quality indicators. The results confirm previous assumptions and the connection between the differential game theory and control problems.
Keywords: differential games; optimal control; approximate dynamic programming